Rescheduling Under Disruptions in Manufacturing Systems Models and Algorithms - Wang, Dujuan; Yin, Yunqiang; Jin, Yaochu (Uncertainty and Operations Research, 2020)
XI, 147 p. 15 illus., 11 illus. in color.